Website-Based Library Visitor Data Collection System Using Face-API - Muhammad Ferdi Firmansyah Firmansyah; Ahmat Josi; Better Swengky (KHARISMA Tech, 2026)
The library plays an important role in supporting academic activities in higher education institutions, including the Politeknik Manufaktur Negeri Bangka Belitung. The existing visitor recording system, which still relies on manual input of Student Identification Numbers (NPM), has proven to be inefficient and prone to input errors. To address this issue, a Library Visitor Data Collection System Based on Facial Recognition was developed to automatically identify visitors using Face Recognition technology through the Face-API.js library. The system is designed as a web-based application, allowing both visitors and administrators to access it in real-time. The development process was carried out using the Rapid Application Development (RAD) method, enabling rapid prototyping and a strong focus on user requirements. The implementation results show that the system improves data collection efficiency, reduces human error, and accelerates the visitor identity verification process. Therefore, this system can serve as a tangible step toward the digitalization and modernization of library administrative services.